Rulers, townsmen and bazaars North Indian society in the age of British expansion, 1770-1870 - Bayly, Christopher Alan 1945-2015 (Oxford University Press, 2012)
This volume traces the evolution of north Indian towns and merchant communities from the decline of Moghul dominion to the consolidation of Britain's empire in India following the 1857 mutiny